A novel approach to determine plastic hardening curves of AA7075 sheet utilizing hydraulic bulging test at elevated temperature. (September 2015) - Liu, Kangning; Lang, Lihui; Cai, Gaoshen; Yang, Xiying; Guo, Chan; Liu, Baosheng
Abstract: Precise estimation of various mechanical properties of sheet metal with strong non-linearities has always been a major problem in process simulation by Finite Element Method (FEM). The hydraulic bulge test as prescribed in ISO standard 16808 is well-known for its capability of obtaining flow stress at higher strain levels compared to uniaxial tensile test, but a more applicable method is also needed to calculate the flow stress properties of bulge test especially at elevated temperature. In this study, a set of explicit integral format formulas based on the classical plastic flow rules were deduced to calculate thickness distribution from the aspect of the mechanics analysis. Afterwards an iterative method combined with integration formulas was established to evaluate hardening curves for specimen. Finally, A group of hydraulic bulge tests were performed using sheet metal of AA7075 alloy at room and elevated temperatures with a constant pressure increasing rate, supplementary tensile tests were also carried out at corresponding conditions to compare with the stress–strain curves from the bulge tests. Result shows that the proposed method can evaluate the flow stress curves of the test specimen with reasonable accuracy and with higher strain range over the temperatures ranging from cold to elevated values. Highlights: Formulas to calculate the dome apex thickness of bulging test. Iteration method to establish the stress‐strain curves of bulding test. Comparison study between tensile and bulging test.